Uwarunkowania efektywnego zarządzania komunalnymi zasobami mieszkaniowymi - przykład Łodzi - Sikora, Dorota (Conditions for Effective Management of Public Housing Resources - on the Example of Łódź, 2007)
The development of housing sector is conditioned by a series of economical and legal factors. The management of district housing resources may be entrusted to real estate administrators, property valuers, real estate agents or enterpreneurs, who employ the above people. In reality, though, the management of property owned or co-owned by the district or by the National Treasury is in the hands of budgetary enterprises - property administrations and housing management companies. The management of housing resources is influenced by numerous factors. The objective of this article is to identify these factors and to define the most common problems of housing in Łódź.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 690-698